2017
DOI: 10.1158/0008-5472.can-16-2432
|View full text |Cite
|
Sign up to set email alerts
|

Superior Efficacy and Selectivity of Novel Small-Molecule Kinase Inhibitors of T790M-Mutant EGFR in Preclinical Models of Lung Cancer

Abstract: The clinical utility of approved EGFR small molecule kinase inhibitors is plagued both by toxicity against wild-type EGFR and by metastatic progression in the central nervous system (CNS), a disease sanctuary site. Here we report the discovery and preclinical efficacy of GNS-1486 and GNS-1481, two novel small molecule EGFR kinase inhibitors that are selective for T790M mutant isoforms of EGFR. Both agents were effective in multiple mouse xenograft models of human lung adenocarcinoma (T790M positive or negative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Next, we examined the effect of vorinostat on gefitinib sensitivity in PC9 and PC9GR cells. In accordance with previous reports (8,9), treatment with 0.01 µM gefitinib alone significantly decreased the viability of PC9 cells, but it had no effect on PC9GR cells ( Fig. 2A, upper graphs).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Next, we examined the effect of vorinostat on gefitinib sensitivity in PC9 and PC9GR cells. In accordance with previous reports (8,9), treatment with 0.01 µM gefitinib alone significantly decreased the viability of PC9 cells, but it had no effect on PC9GR cells ( Fig. 2A, upper graphs).…”
Section: Resultssupporting
confidence: 93%
“…First, we examined the inhibitory effect of the HDACI vorinostat on the viability of NSCLC PC9 and gefitinib-resistant PC9GR cells using a CellTiter-Glo assay. The PC9 cell line has a deletional mutation in EGFR exon 19 and the PC9GR cell line is resistant to gefitinib by having acquired a secondary T790M mutation in EGFR exon 20 (8,9). Exposure to vorinostat efficiently reduced the viability of both cell lines in a concentration-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We previously described a third‐generation EGFR‐TKI (GNS compound) which is similar to osimertinib in terms of its effects on EGFR‐mutant cell lines, xenograft models and selectivity of kinases, but showed a superior intracranial antitumor efficacy (Rho et al ., ). In our analyses in that study, osimertinib as well as GNS compound at 10 mg·kg −1 showed a good response initially, but this was not sustained over time in most of the mice.…”
Section: Discussionmentioning
confidence: 97%
“…We next tested whether the intrathecal injection of NUFS-sErt could efficiently suppress the growth of intracranial HCC827-Luc tumors. We established a mouse model with a HCC827-Luc intracranial xenograft in the left brain, as described previously (Rho et al, 2017). We fixed a screwing device into the right brain ventricles of these animals to enable intrathecal drug injection (Fig.…”
Section: Efficacy Of Nufs-sert In Vivomentioning
confidence: 99%